2014 IEEE 29th Conference on Computational Complexity (CCC) 2014
DOI: 10.1109/ccc.2014.28
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Repetition Theorem for Entangled Projection Games

Abstract: We study the behavior of the entangled value of two-player one-round projection games under parallel repetition. We show that for any projection game G of entangled value 1 − ε < 1, the value of the k-fold repetition of G goes to zero as O((1 − ε c) k), for some universal constant c ≥ 1. If furthermore the constraint graph of G is expanding we obtain the optimal c = 1. Previously exponential decay of the entangled value under parallel repetition was only known for the case of XOR and unique games. To prove the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Matrix approach can, as in Theorem 1.11, also treat tensor product of different games. If we consider a ''quantum version'' of two-prover one-round games, the situation becomes a bit different: Both of information theoretic [13,28] and matrix analysis [18] approaches showed parallel repetition theorems for different classes of games.…”
Section: Tamakimentioning
confidence: 99%
“…Matrix approach can, as in Theorem 1.11, also treat tensor product of different games. If we consider a ''quantum version'' of two-prover one-round games, the situation becomes a bit different: Both of information theoretic [13,28] and matrix analysis [18] approaches showed parallel repetition theorems for different classes of games.…”
Section: Tamakimentioning
confidence: 99%
“…In a different line of work, Dinur, Steurer and Vidick show that projection games (with an arbitrary input distribution) also have an exponential decay in entangled value under parallel repetition: if G be a 2-player projection game with classical inputs and outputs, and val * (G) = 1−ǫ, then val * (G ⊗n ) ≤ (1− ǫ 12 ) Ω(n) [DSV14]. This result is not comparable with our work, nor with the work of [CS14b,JPY14].…”
Section: Related Workmentioning
confidence: 99%
“…This result is known as the Parallel Repetition Theorem, and is central in the study of hardness of approximation, probabilistically checkable proofs, and hardness amplification in classical theoretical computer science.Recently, quantum analogues of the Parallel Repetition Theorem have been studied, and for certain types of games, it has been shown that the entangled game value also goes down exponentially with the number of repetitions. In particular, parallel repetition theorems have been shown for 2-player free games (see [CS14a,CS14b,JPY14]) and projection games (see [DSV14]). Free games are where the input distribution to the players is a product distribution (i.e.…”
mentioning
confidence: 99%
“…Note here that the non trivial part is that Bob's second measurement is applied on the post-measurement state resulting from his first measurement. Because we are in the quantum setting, this first measurement will generally perturb the state shared by Alice and Bob, which makes it non trivial to relate the success probability of this strategy for G coup with the entangled value ω * (G) of the original game G. A similar construction of squared games was introduced in [DS14,DSV15] to study projective classical and entangled games. There, the input x is not revealed to the players but they receive respectively y and y and output b and b .…”
Section: Consecutive Measurementsmentioning
confidence: 99%